Perception of Islamic Scholars towards Polio Vaccination in Northern Nigeria - Suleiman Mohammed Saeed (International Journal of Vaccines, 2024)
Poliomyelitis, commonly known as polio, is a highly infectious disease that can lead to permanent paralysis and, in severe cases, death. Despite global efforts to eradicate polio through vaccination, Nigeria, particularly its Northern region, has faced significant challenges in reaching full immunization coverage. Resistance to polio vaccination is often rooted in cultural and religious concerns, with Islamic scholars playing a significant role in shaping public perception and acceptance of health interventions. This study investigates the attitudes, beliefs, and influence of Islamic scholars towards polio vaccination in Northern Nigeria, where vaccine hesitancy has presented an obstacle to public health initiatives. Using a qualitative research approach, we conducted in-depth interviews with a representative sample of Islamic scholars across several states in Northern Nigeria. The findings reveal that Islamic scholars’ perceptions of polio vaccination are influenced by a complex interplay of religious beliefs, historical mistrust of international health agencies, and the spread of misinformation within communities. While some scholars view vaccination as a religious duty to protect health, others express concerns that the vaccine may conflict with religious or cultural values. Additionally, rumours and conspiracy theories, such as beliefs that the vaccine is a means of population control, have contributed to scepticism among scholars and their communities. This research highlights the pivotal role that Islamic scholars play as community leaders and influencers in Northern Nigeria, particularly in rural and underserved areas. By understanding these scholars’ perspectives, health authorities can tailor communication strategies and collaborate with religious leaders to improve vaccine acceptance. Our findings suggest that culturally sensitive engagement with Islamic scholars, combined with efforts to address misinformation, and could be instrumental in reducing resistance to polio vaccination. The study offers practical recommendations for health policy makers, emphasizing the need for community-based approaches that respect religious beliefs while promoting public health objectives. This research contributes to the broader discourse on health interventions in religious communities and has implications for other regions facing similar challenges with vaccine hesitancy.
Keywords: Islamic scholars; Northern Nigeria; perception; polio; vaccination